Shifting sands on differentiation and specialisation in higher education in South Africa - Ntshoe, I M; Selesho, J M (South African Journal of Higher Education, 2016)
This paper examines shifts in, and variations of, differentiation, diversification and specialisation and their impact on missions and mandates of different institutional types in South Africa. It explores patterns and how these might encourage institutional ‘mission drift’, arguing that, in practice, institutions are positioned on a continuum. While legally mandated institutional boundaries are still common, there is increasing support for the blurring of these boundaries because of changing conditions in the new economy. Mission drift could be attributed to the decline in government funding, increasing private contribution and entrepreneurship.